COVID-19 associated anxiety and perceived risk among the pregnant women: a cross-sectional study - Nooruddin, Shanila; Khan, Tooba Jawed; Nausheen, Sidrah; Nasir, Fouzia; Shaikh, Ghulam Abbas; Shaikh, Asif; Sadiqa, Ayesha; Abbas, Shabnam; Rizvi, Arjumand; Soofi, Sajid; Habib, Muhammad Atif (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 is an infectious disease, categorized as a global pandemic. Daily implications and coping strategies of pregnant women with coronavirus outbreak is currently unknown. This study will assess their knowledge, attitude, and practices (KAP), risk perceptions, anxiety and concerns related to COVID-19. Methods: A hospital-based cross-sectional survey was conducted in Karachi. Self-reported questionnaires including KAP, generalized anxiety disorder (GAD) scale and perception of pregnancy risk questionnaire were administered. Descriptive statistics were calculated for continuous variables and were reported as mean ± standard deviation. Frequencies and percentages were computed for categorical variables. Pearson correlation was calculated to explore linear associations among the perception of pregnancy risk, age, body mass index (BMI), and gestation. All data analysis was done using STATA 16.0. Results: The 575 pregnant women were enrolled with an average age of 26.07 years and 27.22±8.99 gestational age. Their knowledge showed that 92.2% knew that coronavirus causes COVID-19 and 72.30% knew the importance of wearing masks. Regarding attitudes, 96.3% felt safe to breastfeed their newborns, 80.20% considered changing their birth method whereas 54.6% were not concerned about the outbreak and around 70-80% cancelled their social gatherings. 72% trusted healthcare frontline staff with their struggle towards COVID-19. The 43.82% women were more anxious (scoring ≥7) and 56.17% were less anxious (<7) on GAD scale. The mean score for perceived risk for baby and mother was 22.95±13.72 and 19.40±0.57 respectively. Conclusions: Considering the burden of COVID-19, pregnant women’s perception is a major contributor to her and her baby’s health and wellbeing. Well-planned strategies by media, healthcare providers and government would significantly support such pregnant women during COVID-19.